Axiom Preferences and Choice Mistakes under Risk - Fabian Herweg; Svenja Hippel; Daniel Müller; Fabio Römeis (CESifo GmbH, 2024)
We investigate whether violations of canonical axioms of choice under risk are mistakes or a manifestation of true preferences. First, we elicit axiom and gamble preferences and then allow subjects to revise their potentially conflicting preferences. Among the behavioral patterns that allow for a clear-cut interpretation on the decision level, we find that roughly 70% of axiom viola-tions are intentional whereas only 30% are mistakes. On the subject level we can clearly categorize almost half of our subjects. Among those, roughly 24%are rational expected utility maximizers, 24% make occasional mistakes, and 52% refute the normative value of these axioms.
Keywords: C91; D01; D81; D91; 330; axiomatic rationality; choice under risk; context-dependent preferences; mistakes; regret theory